2018
DOI: 10.3889/oamjms.2018.103
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Acute Viral Encephalitis in a Sample of Egyptian Children

Abstract: INTRODUCTION:Acute encephalitis syndrome (AES) is a considerable public health problem.AIM:This study was designed to describe the aetiology, demographic features, clinical picture, short-term outcome and risk factors of mortality of children with viral encephalitis in Egyptian children.METHODS:PCR detection of viruses in the CSF of pediatric patients admitted to the pediatric unit or ICU Cairo University Pediatric hospital presenting with encephalitis syndrome.RESULTS:Of the 96 patients included in the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
3
9
1
3
Order By: Relevance
“…In our study, an estimated length of stay of patients with encephalitis in the intensive care unit was 5.45±2.62 days. In comparison to our study, Sonneville et al ( 20 ) in 2015 also concluded that the duration of stay in the intensive care unit was estimated to be 9 days (5–22 days).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In our study, an estimated length of stay of patients with encephalitis in the intensive care unit was 5.45±2.62 days. In comparison to our study, Sonneville et al ( 20 ) in 2015 also concluded that the duration of stay in the intensive care unit was estimated to be 9 days (5–22 days).…”
Section: Discussioncontrasting
confidence: 59%
“…According to the study conducted by Sonneville et al ( 4 ), 42 % patients with encephalitis need mechanical ventilation at the time of admission, and 13% of patients needs mechanical ventilation thereafter. In another study conducted on children with encephalitis, 44.8% patients required mechanical ventilation ( 20 ). In 2017, a study was conducted in India which concluded that 42% patients with encephalitis need invasive ventilation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kirti Gupta et al (2) showed that GCS < 8, shock, raised intracranial tension and respiratory failure were the risk factors associated with higher mortality. Meligy and his colleagues in Egypt in 2018 (10) showed mechanical ventilation was a risk factor for fatality.…”
Section: Discussionmentioning
confidence: 99%
“…Satu penelitian juga menunjukkan mayoritas pasien ensefalitis adalah laki-laki. 2 Infeksi HIV dapat menjadi faktor risiko, meningkatkan mortalitas, memperburuk prognosis, dan memengaruhi keberhasilan terapi pada infeksi SSP. 21,22 Prevalensi pasien yang tidak mengetahui status imunisasi BCG masih cukup tinggi, yaitu 21,4 % pada pasien meningitis TB dan 33,3% pada pasien meningoensefalitis.…”
Section: Pembahasanunclassified
“…Terdapat literatur yang menyatakan bahwa pasien dengan ensefalitis viral rata-rata terjadi pada usia 29 bulan. 2 Awitan gejala meningitis TB pada anak cenderung beragam sesuai dengan hasil penelitian. Mayoritas memiliki awitan sub-akut, hal ini disebabkan oleh gejala awal yang sering menyerupai penyakit lain sehingga mempersulit diagnosis.…”
Section: Pembahasanunclassified